Unlawful Administrative Act: Indonesian Administrative Law Perspective - Putu Gede Arya Sumerta Yasa; Wita Setyaningrum; Kadek Agus Sudiarawan (Varia Justicia, 2021)
This study aims to analyze and examine the meaning of unlawful acts by government officials and the authority of state administrative courts in dealing with cases related to unlawful acts by government officials. This study was normative legal research using a statutory approach and a conceptual approach. The primary legal materials uses in this study including Indonesian Civil Code (Burgerlijk Wetboek), Supreme Court Regulation (hereinafter PERMA) Number 2 of 2019 concerning Guidelines For Dispute Settlement Of Government Actions and Authority to Hearing Unlawful Acts By A Government Board And Government Officer (onrechtmatige overheidsdaad) and Law No. 51 of 2009 concerning the second amendment to Law Number 5 of 1986 concerning State Administrative Court to analyses substance related to the meaning of unlawful acts by government officials and the authority of state administrative courts in dealing with cases related to unlawful acts by government officials in accordance with prevailing law. The conceptual approach taken from the meaning of onrechmatigedaad in Burgerlijk Wetboek. This study indicated that the dispute settlement on the unlawful act by the government official mentioned on the Supreme Court regulation (hereinafter PERMA) number 2 of 2019 including dispute settlement process, which shall be file through state administrative court. which stipulates that the authority to hearing the disputes of unlawful acts by the government board or the government officials can be resolved through the state administrative judiciary.